2000
DOI: 10.1523/jneurosci.20-08-02896.2000
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Infusion of IGF-I Selectively Induces Neurogenesis in the Adult Rat Hippocampus

Abstract: In several species, including humans, the dentate granule cell layer (GCL) of the hippocampus exhibits neurogenesis throughout adult life. The ability to regulate adult neurogenesis pharmacologically may be of therapeutic value as a mechanism for replacing lost neurons. Insulin-like growth factor-I (IGF-I) is a growth-promoting peptide hormone that has been shown to have neurotrophic properties. The relationship between IGF-I and adult hippocampal neurogenesis is to date unknown. The aim of this study was to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
483
4
9

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 767 publications
(517 citation statements)
references
References 71 publications
21
483
4
9
Order By: Relevance
“…It is possible that the muscarinic signaling cascade may be part of, and/ or play a synergistic role to, the cytokine system, whose role in neurogenesis has been suggested by other investigators. [11][12][13][14][15] Whether neurogenesis was causative of biochemical recovery, most importantly of PKC, or merely parallel thereof, remains a subject of future investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that the muscarinic signaling cascade may be part of, and/ or play a synergistic role to, the cytokine system, whose role in neurogenesis has been suggested by other investigators. [11][12][13][14][15] Whether neurogenesis was causative of biochemical recovery, most importantly of PKC, or merely parallel thereof, remains a subject of future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is the induction of cytokines by neural progenitors, [8][9][10] which enhance proliferation of endogenous neural cells. [11][12][13][14][15] Here, we aimed to examine our hypothesis by employing the prenatally heroin-damaged brain model. The heroin model was chosen because, among other effects, it induces deficits that can be related to specific synaptic functions.…”
Section: Introductionmentioning
confidence: 99%
“…A second approach using electrophysiology to measure from GFP-retrovirally labeled cells showed that integrated neurons exhibited neuronal morphology and displayed passive membrane properties and action potentials (Song et al, 2002;van Praag et al, 2002). Furthermore, neurogenesis in the hippocampus can be induced by exogenous factors, including peripheral administration of insulin-like growth factor-I (IGF-I) (Aberg et al, 2000) or hormones like corticosteroids (Tanapat et al, 1999;Gass et al, 2000), enriched environment (Kempermann et al, 1997;Nilsson et al, 1999), exercise (van Praag et al, 1999a,b;Gould et al, 2000), or interestingly, by hypoxia (Liu et al, 1998). Unfortunately, none of these reports has demonstrated that these signals can be used as strategies for regeneration in humans.…”
Section: Physiological Function and Regulation Of Cns Stem Cellsmentioning
confidence: 99%
“…61 Selective induction of neurogenesis has also been achieved using IGF-1. 62,63 Further studies should elucidate the possible involvement of these molecules in the mechanism of action of tianeptine and other antidepressants.…”
Section: Neurobiological Properties Of Tianeptinementioning
confidence: 99%